Ecosystem services game: Game Design Document - Zanzanaini, Camilla; Miller, Brett A.; Everett, Pete; Carella, Antonio (CGIAR Research Program on Water, Land and Ecosystems, 2014)
This is a serious game about ecosystem services. The intention is to raise awareness and teach players about integrated landscape management and ecosystem services in a fun and interactive way. By making choices, observing outcomes and adjusting strategy, players will learn how to maximize benefits from specific ecosystem services using different management tactics. The game is intended to be part of an educational pack that includes learning modules, case studies or other useful teaching resources.